Original delayed-start ovarian stimulation protocol with a gonadotropin-releasing hormone antagonist, medroxyprogesterone acetate, and high-dose gonadotropin for poor responders and patients with poor-quality embryos - Takeuchi, Kazuhiro; Orita, Yuji; Iwakawa, Tokiko; Kuwatsuru, Yukari; Kuroki, Yuko; Fukumoto, Yumiko; Mizobe, Yamato; Tokudome, Mari; Moewaki, Harue (Frontiers in Endocrinology, 2023)
Introduction The delayed-start gonadotropin-releasing hormone antagonist protocol seems effective for patients who are poor ovarian responders, but there are insufficient data on whether it is also effective for patients with poor-quality embryos and low rates of good blastocyst formation. Specifically, the effectiveness of delayed-start gonadotropin-releasing hormone antagonists with progesterone has not been adequately investigated. Therefore, we compared the efficacy of the original delayed-start gonadotropin-releasing hormone antagonist protocol using medroxyprogesterone acetate (MPA) and high-dose gonadotropin in patients with poor ovarian response. Methods Overall, 156 patients with recurrent assisted reproductive technology failure who underwent the original protocol were included. They received cetrorelix acetate (3 mg) and MPA (10 mg) on cycle day 3, and high-dose gonadotropin was initiated on day 11. When the leading follicle reached 14 mm, ganirelix acetate (0.25 mg) was administered until the trigger day. The number of oocytes retrieved, metaphase II (MII) oocytes, two pronuclear (2PN) zygotes, and good blastocysts and live birth rates were compared between the previous (Cycle A) and original (Cycle B) cycles in three groups (Group A, all patients; Group B, poor responders; and Group C, patients with poor-quality embryos). Results In Group A (n=156), the number of MII oocytes (3.6 ± 3.3 versus 4.5 ± 3.6), 2PN zygotes (2.8 ± 2.9 versus 3.8 ± 3.1), good blastocysts (0.5 ± 0.9 versus 1.2 ± 1.6), and live birth rates (0.6 versus 24.4) significantly increased in Cycle B. Similar results were obtained in Group B (n=83; 2PN zygotes [1.7 ± 1.7 versus 2.3 ± 1.8], good blastocysts [0.4 ± 0.7 versus 0.9 ± 1.3], live birth rates [0 versus 18.1]) and Group C (n=73; MII oocytes [5.1 ± 3.8 versus 6.6 ± 4.0], 2PN zygotes [4.0 ± 3.4 versus 5.4 ± 3.4], good blastocysts [0.7 ± 1.1 versus 1.6 ± 1.9], and live birth rates [1.4 versus 31.5]). Conclusion This original protocol increased the number of MII oocytes retrieved, 2PN zygotes, good blastocysts, and live birth rates in both poor responders and in patients with poor-quality embryos.